The novel KIT exon 11 germline mutation K558N is associated with gastrointestinal stromal tumor, mastocytosis, and seminoma development. Issue 12 (20th August 2021) - Meir, Michael; Maurus, Katja; Kuper, Jochen; Hankir, Mohammed; Wardelmann, Eva; Rosenwald, Andreas; Germer, Christoph‐Thomas; Wiegering, Armin
Abstract: Familial gastrointestinal stromal tumors (GIST) are dominant genetic disorders that are caused by germline mutations of the type III receptor tyrosine kinase KIT. While sporadic mutations are frequently found in mastocytosis and GISTs, germline mutations of KIT have only been described in 39 families until now. We detected a novel germline mutation of KIT in exon 11 (p.Lys‐558‐Asn; K558N) in a patient from a kindred with several GISTs harboring different secondary somatic KIT mutations. Structural analysis suggests that the primary germline mutation alone is not sufficient to release the autoinhibitory region of KIT located in the transmembrane domain. Instead, the KIT kinase module becomes constitutively activated when K558N combines with different secondary somatic mutations. The identical germline mutation in combination with an additional somatic KIT mutation was detected in a second patient of the kindred with seminoma while a third patient within the family had a cutaneous mastocytosis. These findings suggest that the K558N mutation interferes with the juxtamembranous part of KIT, since seminoma and mastocystosis are usually not associated with exon 11 mutations.